2023
DOI: 10.18196/jesp.v23i2.15859
|View full text |Cite
|
Sign up to set email alerts
|

Do Poverty and Economic Growth Matter for Income Inequality Reduction in Yogyakarta Province?

Abstract: It has been observed that income inequality is an economic element that may impede a nation's economic development. In general, Indonesia's Gini ratio has remained low for nearly a decade, although one region, Yogyakarta Province, unexpectedly exceeds the national average. The provincial government of Yogyakarta must focus more on reducing income inequality. Therefore, this study employs the Poverty-Growth-Inequality Triangle model approach to investigate the complexity of income inequality in Yogyakarta Provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Indikator tingkat tabungan yang dimiliki masyarakat memiliki nilai yang positif, artinya hal tersebut ada hubungannya antara ketimpangan pendapatan masyarakat dengan pertumbuhan ekonomi. Maurilla, Suriani, & Nasir (2022) menemukan bahwa adanya ketimpangan pendapatan sebagai salah satu faktor penghambat pembangunan dan perkembangan ekonomi disuatu negara. Rasio Gini atau Koefisien Gini ditetapkan sebagai indikator pengukuran kesenjangan pendapatan secara umum berlaku diseluruh dunia.…”
Section: Ketimpangan Ekonomiunclassified
See 1 more Smart Citation
“…Indikator tingkat tabungan yang dimiliki masyarakat memiliki nilai yang positif, artinya hal tersebut ada hubungannya antara ketimpangan pendapatan masyarakat dengan pertumbuhan ekonomi. Maurilla, Suriani, & Nasir (2022) menemukan bahwa adanya ketimpangan pendapatan sebagai salah satu faktor penghambat pembangunan dan perkembangan ekonomi disuatu negara. Rasio Gini atau Koefisien Gini ditetapkan sebagai indikator pengukuran kesenjangan pendapatan secara umum berlaku diseluruh dunia.…”
Section: Ketimpangan Ekonomiunclassified
“…Ketimpangan Penulis 1 Ketimpangan sosial (Attamimi, Kinseng, & Agusta, 2018); (Camarero & Olivia, 2019); (Elenbaas, Rizzo, & Killen, 2022); (Hernovianty, Pratiwi, & Adventia, 2021). 2 Ketimpangan ekonomi (Hill, 2021); (Itskovich & Factor, 2023); (Maurilla, Suriani, & Nasir, 2022); (Mdingi & Ho, 2021); (Sulistyaningrum & Tjahjadi, 2022). 3 Ketimpangan budaya (Ali & Byrne, 2023); (Saifuddin, 2017); (Supraptiningsih, Jubba, Hariyanto, & Rahmawati, 2023); (Nurman, Yusriadi, & Hamim, 2022).…”
Section: Ketimpangan Multisektor DI Indonesiamentioning
confidence: 99%
“…Income inequality is a significant issue in Yogyakarta Province, Indonesia, despite its cultural heritage and economic potential. The provincial government of Yogyakarta needs to focus on reducing income inequality [1]. The study suggests that education and the district minimum wage have a significant impact on income inequality in the region [2].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies provide insights into this issue. According to [1], education and district minimum wage have a significant impact on income inequality in Yogyakarta Province. [6] found that factors such as household consumption, exports, foreign investment, and per capita income have a positive effect on inclusive economic growth, which can help reduce income inequality.…”
Section: Introductionmentioning
confidence: 99%